(untitled) (Global Journal of Management and Business Research, 2023)
Purpose The objective of this work is to propose a business process management maturity model BPMMM prescriptive and with multicriteria decision-making approach MCDM Design Methodology Approach The relevant literature was examined to develop BPMMM The Analytic Hierarchy Process AHP method was chosen to evaluate the weight of the capabilities The Fuzzy Technique for Order Preference by Similarity to Ideal Solution TOPSIS method measured the maturity level The model was applied in property divisions DIPAT of two federal universities public institutions with comparative and prescriptive purpose Reference DIPAT and Real DIPAT